Prodigal Prodigy. - Houellebecq, Michel; Ridley, Matt; Huxley, A; Ballard, J.G; Márai, S.; Thek, Paul; Sirota, Lyubov; White Box, New York City ([S.l.] : TT Inc, 2003)
Ackermann, Rita ; Alvi, Tariq ; Breitz, Candice ; ter Heyne, Mathilde ; Raeven, L.A. ; Rothschild, Eva ; Sato, Keiko ; Speakman, William ; Thek, Paul ; Williams, John ; Valdes, Juana
Book was publised as part of the exhibition 'prodigal prodigy' at White Box NYC, 9-7 / 10-20-2001
kunstcatalogus